Nitrogen in-situ doped supercapacitor electrode material and preparation method and application thereof

By doping coal liquefied residue with high nitrogen-containing Urchin, nitrogen in situ doped supercapacitor electrode materials are prepared, which solves the problem of single and low value utilization of coal liquefied residues, and the preparation and large-scale production of high-performance supercapacitor electrode materials are achieved.

CN119742185APending Publication Date: 2025-04-01KUNMING UNIV OF SCI & TECH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411938412.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, coal liquefied residues are used in a single way and have low value, and the specific capacitance of capacitor electrode materials is relatively low, making it difficult to meet the needs of high-performance supercapacitors.

Method used

By cooperating the coal liquefied residue with the high nitrogen-containing Urethra as a precursor, in situ doping, introducing nitrogen atoms, and preparing nitrogen in situ doped supercapacitor electrode material. The method includes carbonization, impregnation, activation and washing neutral process treatment.

Benefits of technology

The waste utilization of liquefied residues and Ulcers was achieved, and electrode materials with high electrochemical performance were obtained. The material has a large specific surface area, reasonable distribution of micropores and mesoporous pores, good hydrophilicity, simple operation, low cost, and large-scale production can be achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742185A_ABST
    Figure CN119742185A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coal liquefaction residue utilization, in particular to a nitrogen in-situ doped supercapacitor electrode material and a preparation method and application thereof. According to the invention, the coal liquefaction residue is used as a main raw material, and biomass such as enteromorpha with high nitrogen content is mixed with the coal liquefaction residue to obtain the nitrogen-doped high-end supercapacitor electrode material, so that the utilization rate and the additional value of the residue can be improved, the electrochemical performance of the electrode material is improved, and when the current density is 1A g <-1 >, the specific capacitance of the electrode can reach 200F g <-1 >; after 5000 times of charge and discharge cycles, the capacitance retention rate can reach 95.6%, and the material has good cycle characteristics and good stability, and has application prospects in capacitor energy storage devices and electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coal liquefaction residue utilization, and in particular to a nitrogen in-situ doped supercapacitor electrode material and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Coal liquefaction residues are byproducts produced during the coal liquefaction process, usually containing various chemicals and energy values. These residues can be used in a variety of ways. For example, coal liquefaction residues may contain certain combustible substances, which can be used as fuel and burned in thermal power plants to generate heat and electricity; they can be used to produce building materials such as bricks, tiles and concrete; they can be used as mineral supplements and used as raw materials in cement production; they can be used as road base materials or pavement materials to improve road performance and reduce the demand for traditional materials; or they can be used to extract and produce chemical products such as fertilizers, asphalt, paint, etc. However, the composition of coal liquefaction residues is complex, and its utilization method depends on its specific composition, properties, and local economic and environmental conditions. Considering the influence of environmental factors, it is difficult to achieve large-scale and high-end utilization when choosing the utilization method. On the other hand, liquefaction residues have a high carbon content, a wide range of sources, a high carbon content (>90%), rich aromatic rings, and low cost. They can be used as a carbon source to prepare carbon materials.

[0004] At present, capacitor electrode materials are generally prepared from carbon electrodes with a single carbon source, which has the difficulty of low specific capacitance. Therefore, preparing a supercapacitor electrode material with superior electrochemical properties is an urgent problem to be solved by technicians in this field. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a nitrogen in-situ doped supercapacitor electrode material and a preparation method and application thereof. Nitrogen atoms are in-situ doped by using biomass such as high-nitrogen-containing Enteromorpha and liquefied residue as precursors, thereby realizing in-situ embedding of nitrogen atoms in the carbon material skeleton, thereby obtaining a high-end supercapacitor electrode material prepared by doping with nitrogen elements. The introduction of nitrogen atoms is beneficial to improving the wettability of the carbon material and enhancing the effective contact and utilization in the electrolyte solution. Not only can the waste utilization of liquefied residue and Enteromorpha be effectively realized, but also an electrode material with high electrochemical performance can be obtained.

[0006] Specifically, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a method for preparing a nitrogen in-situ doped supercapacitor electrode material, specifically: coal liquefaction residue is used as a main carbon source material, and Enteromorpha is used as a nitrogen source and secondary carbon source material, the coal liquefaction residue and Enteromorpha are mixed, and then carbonization, impregnation, activation and neutral washing processes are carried out in sequence to obtain a nitrogen in-situ doped supercapacitor electrode material.

[0008] Preferably, the coal liquefaction residue is tetrahydrofuran insoluble matter produced in the coal liquefaction process, and has a carbon content of 80% to 90%; the enteromorpha has a carbon content of 25 to 30% and a nitrogen content of about 3 to 4%.

[0009] Preferably, the mass ratio of the coal liquefaction residue to Enteromorpha is 1:0.2-0.5.

[0010] Preferably, the coal liquefaction residue and enteromorpha are dried, ground and sieved before mixing; the specific operation is to mix the coal liquefaction residue that is dried at 90-120°C for 1-2 hours and then crushed through a 50-mesh sieve with the enteromorpha that is vacuum dried at 95-125°C for 2-5 hours and then ground through a 100-mesh sieve.

[0011] Preferably, the carbonization and activation are performed under an inert atmosphere, and more preferably, the inert atmosphere is nitrogen.

[0012] Preferably, the carbonization temperature is 400-600° C. and the time is 1-2 hours.

[0013] Preferably, the impregnation is to grind the carbonized material, add an activator to form a solution and stir; further preferably, the activator is selected from one or more of KOH, NaOH, ZnCl2 and K2CO3; further preferably, the activator is KOH.

[0014] Preferably, the mass ratio of the activator to the carbonized material is 2:1 to 4:1.

[0015] Preferably, the activation temperature is 700-900° C. and the activation time is 1-1.5 h.

[0016] Preferably, the solvent used in the pickling process is selected from one or more of hydrochloric acid and nitric acid; further preferably, the solvent is hydrochloric acid.

[0017] Preferably, the neutralization washing process specifically comprises acidifying and neutralizing the activated material, washing it with deionized water until it is neutral, and then drying it at 95 to 120° C. for 2 to 4 hours and then fully grinding it to obtain a nitrogen in-situ doped supercapacitor electrode material.

[0018] The second aspect of the present invention provides a nitrogen in-situ doped supercapacitor electrode material, which is prepared by the preparation method of the nitrogen in-situ doped supercapacitor electrode material described in the first aspect.

[0019] The third aspect of the present invention provides a battery negative electrode, comprising the nitrogen in-situ doped supercapacitor electrode material prepared by the preparation method described in the first aspect as an active material.

[0020] Preferably, the battery negative electrode further comprises a conductive material, a binder and an organic solvent;

[0021] Wherein, the conductive material is selected from one or more of acetylene, acetylene black, and conductive graphite, and is more preferably conductive graphite;

[0022] The binder is one or more of polytetrafluoroethylene (PVDE) and polyvinylidene fluoride (PVDF), and more preferably polytetrafluoroethylene (PVDE);

[0023] The organic solvent is selected from one or more of ethanol, 1-methyl-2-pyrrolidone, and N-methylpyrrolidone, and is more preferably ethanol.

[0024] Preferably, the mass ratio of the active substance, the conductive material and the binder is 7:1:1 to 9:1:1; further preferably, the mass ratio of the active substance, the conductive material and the binder is 8:1:1.

[0025] A fourth aspect of the present invention provides a supercapacitor comprising the battery negative electrode described in the third aspect.

[0026] Preferably, the supercapacitor further comprises a positive electrode, a separator, and an electrolyte;

[0027] Further preferably, the electrolyte is a 6M KOH solution.

[0028] A fifth aspect of the present invention provides an application of the nitrogen in-situ doped supercapacitor electrode material described in the second aspect in capacitor energy storage devices and electrode materials.

[0029] One or more technical solutions of the present invention have the following beneficial effects:

[0030] (1) In view of the problem that the existing liquefaction residue utilization method is single and of low value, the present invention provides a method for preparing supercapacitor electrode materials by in-situ nitrogen doping of liquefaction residue. The prepared supercapacitor material has a large specific surface area, a reasonable distribution of micropores and mesopores, good hydrophilicity, simple operation, low cost, and can be mass-produced.

[0031] (2) After adding high-nitrogen-content Enteromorpha, the present invention makes the activated carbon prepared from the liquefied residue have a developed pore structure and a reasonable pore size distribution. At the same time, the introduction of nitrogen atoms into the carbon skeleton can enhance the hydrophilicity of the carbon material and increase its energy storage sites. The substitution of nitrogen can further increase the electron transfer rate.

[0032] (3) The supercapacitor electrode material prepared by the preparation method of the present invention has good electrochemical performance. When the current density is 1A -1 When the electrode specific capacitance reaches 200F g -1 After 5000 charge and discharge cycles, the capacitance retention rate can reach 95.6%, which has good cycle characteristics and good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0034] Figure 1 The X-ray diffraction spectrum (XRD) of the supercapacitor material prepared in Example 1 of the present invention;

[0035] Figure 2 This is a scanning electron microscope (SEM) image of the supercapacitor material prepared in Example 1 of the present invention, wherein (a) is a 500nm surface morphology, and (b) is a local magnified image of (a);

[0036] Figure 3 This is an adsorption-desorption curve (BET) of the supercapacitor material prepared in Example 1 of the present invention;

[0037] Figure 4 This is a pore size distribution diagram of the supercapacitor material prepared in Example 1 of the present invention;

[0038] Figure 5 The electrochemical performance curve (CV) of the supercapacitor material prepared in Example 1 of the present invention;

[0039] Figure 6 This is a GCD curve diagram of the supercapacitor material prepared in Example 1 of the present invention;

[0040] Figure 7 Adsorption-desorption curve (BET) of the capacitor material prepared in Comparative Example 8 of the present invention

[0041] Figure 8 This is the pore size distribution diagram of the capacitor material prepared in Comparative Example 8 of the present invention. DETAILED DESCRIPTION

[0042] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0043] As mentioned above, in order to solve the problem that the existing coal liquefaction residue is of low-end utilization and low value, the present invention provides a method for preparing supercapacitor electrode material by doping liquefaction residue with Enteromorpha and its application; specifically, coal-based liquefaction residue is used as a carbon source, doped with biomass solid waste Enteromorpha, subjected to high-temperature carbonization, chemical impregnation, high-temperature activation, followed by acidification and neutralization, and drying treatment, to obtain high-performance supercapacitor electrode material, which can be further assembled into a supercapacitor.

[0044] The first typical embodiment of the present invention provides a method for preparing a nitrogen in-situ doped supercapacitor electrode material, specifically: coal liquefaction residue is used as the main carbon source material, and Enteromorpha is used as the nitrogen source and secondary carbon source material, the coal liquefaction residue and Enteromorpha are mixed, and then carbonization, impregnation, activation and neutral washing processes are carried out in sequence to obtain a nitrogen in-situ doped supercapacitor electrode material.

[0045] In one or more examples of this implementation mode, the coal liquefaction residue is tetrahydrofuran insoluble matter produced during the coal liquefaction process, and has a carbon content of 80% to 90%; the enteromorpha has a carbon content of 25 to 30% and a nitrogen content of about 3 to 4%.

[0046] In one or more examples of this implementation mode, the mass ratio of the coal liquefaction residue to the enteromorpha is 1:0.2-0.5.

[0047] In one or more embodiments of this implementation mode, the coal liquefaction residue and the enteromorpha are dried, ground and sieved before mixing; the specific operation is to mix the coal liquefaction residue that is dried at 90-120°C for 1-2 hours and then crushed through a 50-mesh sieve with the enteromorpha that is vacuum dried at 95-125°C for 2-5 hours and then ground through a 100-mesh sieve.

[0048] In one or more examples of this embodiment, the carbonization and activation are performed under an inert atmosphere.

[0049] In one or more examples of this embodiment, the inert atmosphere is nitrogen.

[0050] In one or more examples of this embodiment, the carbonization temperature is 400-600° C. and the time is 1-2 hours.

[0051] In one or more examples of this embodiment, the impregnation is to grind the carbonized material, add an activator to the material and mix it into a solution, and then stir it.

[0052] In one or more examples of this embodiment, the activator is selected from one or more of KOH, NaOH, ZnCl2 and K2CO3.

[0053] In one or more examples of this embodiment, the activator is KOH.

[0054] In one or more examples of this implementation, the mass ratio of the activator to the carbonized material is 2:1 to 4:1.

[0055] In one or more examples of this embodiment, the activation temperature is 700-900° C., and the activation time is 1-1.5 hours.

[0056] In one or more examples of this embodiment, the solvent used in the acidification process is selected from one or more of hydrochloric acid and nitric acid.

[0057] In one or more examples of this embodiment, the solvent is hydrochloric acid.

[0058] In one or more embodiments of this implementation, the neutralization washing process specifically includes acidifying and neutralizing the activated material, washing it with deionized water until it is neutral, and then drying it at 95-120°C for 2-4 hours and fully grinding it to obtain nitrogen in-situ doped supercapacitor electrode material.

[0059] A second typical embodiment of the present invention provides a nitrogen in-situ doped supercapacitor electrode material, which is prepared by the above-mentioned method for preparing the nitrogen in-situ doped supercapacitor electrode material.

[0060] A third typical embodiment of the present invention provides a battery negative electrode, comprising the nitrogen in-situ doped supercapacitor electrode material prepared by the above preparation method as an active material.

[0061] In one or more examples of this implementation, the battery negative electrode further includes a conductive material, a binder and an organic solvent;

[0062] Wherein, the conductive material is selected from one or more of acetylene, acetylene black, and conductive graphite;

[0063] The binder is one or more of polytetrafluoroethylene (PVDE) and polyvinylidene fluoride (PVDF);

[0064] The organic solvent is selected from one or more of ethanol, 1-methyl-2-pyrrolidone, and N-methylpyrrolidone.

[0065] Preferably, the mass ratio of the active material, the conductive material and the binder is 7:1:1 to 9:1:1.

[0066] In one or more examples of this implementation mode, the mass ratio of the active material, the conductive material and the binder is 8:1:1.

[0067] A fourth typical embodiment of the present invention provides a supercapacitor, comprising the above-mentioned battery negative electrode.

[0068] In one or more examples of this implementation, the supercapacitor further includes a positive electrode, a separator, and an electrolyte;

[0069] In one or more examples of this embodiment, the electrolyte is a 6M KOH solution.

[0070] A fifth typical implementation of the present invention provides an application of the above-mentioned nitrogen in-situ doped supercapacitor electrode material in capacitor energy storage devices and electrode materials.

[0071] The liquefaction residue described in the present invention is a by-product of the coal liquefaction process and has a large output; Enteromorpha is also a biomass organic solid waste and is difficult to handle. Using the two as raw materials, the sources are wide and the price is low, which broadens the application of coal-based liquefaction residue in the fields of high-value supercapacitors and the like; after adding Enteromorpha with a high nitrogen content, on the one hand, the activated carbon prepared from the liquefaction residue has a developed pore structure and a reasonable pore size distribution, and at the same time, the introduction of nitrogen atoms into the carbon skeleton can enhance the hydrophilicity of the carbon material and increase its energy storage sites, and the substitution of nitrogen can further increase the electron transfer rate.

[0072] The coal liquefaction residue of the present invention mainly comes from tetrahydrofuran insolubles after coal liquefaction, and has a higher carbon content (80%-90%), which is more suitable as a carbon source than the carbon content of traditional biomass; the Enteromorpha as biomass itself can be used as a carbon source, but in the present invention it is mainly introduced and utilized as a nitrogen source, the raw material source is wide, the price is low, and the introduction of other elements is avoided.

[0073] The residue of the present invention is used as the main carbon source, and Enteromorpha is introduced as the nitrogen source and secondary carbon source. If there is too much Enteromorpha, the quality of the material after carbonization will be insufficient, and if there is too little Enteromorpha, there will be no obvious nitrogen enhancement effect. Limiting the proportion of Enteromorpha to 20-50% can better exert the nitrogen source effect of Enteromorpha.

[0074] The present invention places the mixed raw materials in a nitrogen atmosphere to avoid combustion caused by contact with high temperature outside air. The carbonization temperature is mainly pyrolyzed at 400-600°C for 1-2h, which can effectively carry out carbonization. If the temperature is too high, energy consumption will increase, and if the temperature is too low, pyrolysis cannot be complete.

[0075] The mass ratio of potassium hydroxide to carbonized material in the present invention is 2:1 to 4:1. Too much potassium hydroxide will increase consumption and increase the neutral load of washing in the later stage; too low a mass ratio will not effectively impregnate the carbonized material and will not achieve the effect of pore expansion.

[0076] In the present invention, during the material activation, the material is activated at 700-900° C. for 1-1.5 hours. Too low a temperature and too short a reaction time are not conducive to activation and pore formation, while too high a temperature and too long a reaction time result in waste.

[0077] The present invention carries out the neutral washing process in order to remove the excess potassium hydroxide in the pores, further release the pores, and keep the material neutral so that it can be used as a supercapacitor electrode material.

[0078] The electrode material assembly prepared by the present invention mainly comprises the following steps: mixing the obtained active material with conductive graphite and polytetrafluoroethylene in a mass ratio of 7:1:1 to 9:1:1, adding a proper amount of solvent (ethanol), grinding the mixture into a uniform slurry in an agate mortar, coating the mixture on a foam nickel current collector, and drying the mixture in a 60° C. forced air drying oven for 12 hours. After drying, the electrode sheets are formed by a sheet pressing machine, and further combined with an electrolyte to complete the assembly of a supercapacitor.

[0079] As shown in Table 1, the present invention analyzes the elements of coal liquefaction residue and Enteromorpha biomass:

[0080] Table 1

[0081]

[0082] In order to enable those skilled in the art to more clearly understand the technical solution of the present disclosure, the technical solution of the present disclosure will be described in detail below in combination with specific embodiments and comparative examples.

[0083] Example 1 :This embodiment provides a nitrogen in-situ doped supercapacitor electrode material and a preparation method thereof, comprising the following steps:

[0084] (1) Using coal liquefaction residue as the main carbon source material, 5 g of dried coal liquefaction residue raw material and 2 g of Enteromorpha biomass were mixed;

[0085] (2) placing the mixed raw materials in a tubular furnace and pyrolyzing and carbonizing them at 550° C. for 1.5 h under a nitrogen atmosphere; the carbonized carbon material collected was about 30% of the raw materials, i.e., 2.1 g;

[0086] (3) 2 g of the carbonized carbon material was ground and mixed with 6 g of potassium hydroxide activator (mass ratio of 1:3) to prepare a 100 mL solution, which was then fully stirred;

[0087] (4) The impregnated material was filtered, dried at 105°C for 1 h, and placed in a tube furnace for activation at 750°C for 1.5 h under a nitrogen atmosphere;

[0088] (5) The activated material is neutralized with hydrochloric acid, washed with deionized water until neutral, and dried at 105°C for 4 hours. The dried material is then fully ground to obtain high-performance activated carbon, which can be used as a supercapacitor electrode material.

[0089] like Figure 1As shown, it can be seen from the XRD diagram that the main components of the supercapacitor material prepared by this embodiment are carbon, corresponding to the corresponding carbon peak; Figure 2 As shown in the SEM image, it can be observed that the pore structure of the supercapacitor material prepared in this embodiment contains a large number of micropores and mesopores, and the specific surface is rough; Figure 3 As shown, the BET adsorption-desorption curve contains micropores and mesopores; Figure 4 As shown, the pore size is distributed in micropores (less than 2 nm) and mesopores (2-50 nm). Therefore, the distribution of micropores and mesopores of the supercapacitor material prepared in this embodiment is relatively rich and reasonable, providing a favorable channel for the subsequent transmission of electrolytes in the pores. Example 2 :This embodiment provides a nitrogen in-situ doped supercapacitor electrode material and a preparation method thereof, comprising the following steps:

[0090] (1) Using coal liquefaction residue as a carbon source material, 5 g of dried coal liquefaction residue raw material and 1 g of Enteromorpha biomass were mixed;

[0091] (2) placing the mixed raw materials in a tubular furnace and pyrolyzing and carbonizing them at 550° C. for 1.5 h under a nitrogen atmosphere; the carbonized carbon material collected was about 30% of the raw materials, i.e., 1.8 g;

[0092] (3) 2 g of the carbonized carbon material was ground and mixed with 6 g of potassium hydroxide activator (mass ratio of 1:3) to prepare a 100 mL solution, which was then fully stirred;

[0093] (4) The impregnated material was filtered, dried at 105°C for 1 h, and placed in a tube furnace for activation at 750°C for 1.5 h under a nitrogen atmosphere;

[0094] (5) The activated material is neutralized with hydrochloric acid, washed with deionized water until neutral, and dried at 105°C for 4 hours. The dried material is then fully ground to obtain high-performance activated carbon, which can be used as a supercapacitor electrode material.

[0095] Comparative Example 1 :This comparative example provides a nitrogen in-situ doped super capacitor electrode material and a preparation method thereof, comprising the following steps:

[0096] (1) Using coal liquefaction residue as a carbon source material, 5 g of dried coal liquefaction residue raw material and 3 g of Enteromorpha biomass were mixed;

[0097] (2) placing the mixed raw materials in a tubular furnace and pyrolyzing and carbonizing them at 550° C. for 1.5 h under a nitrogen atmosphere; the carbonized carbon material collected was about 30% of the raw materials, i.e., 2.4 g;

[0098] (3) 2 g of the carbonized carbon material was ground and mixed with 6 g of potassium hydroxide activator (mass ratio of 1:3) to prepare a 100 mL solution, which was then fully stirred;

[0099] (4) The impregnated material was filtered, dried at 105°C for 1 h, and placed in a tube furnace for activation at 750°C for 1.5 h under a nitrogen atmosphere;

[0100] (5) The activated material is neutralized with hydrochloric acid, washed with deionized water until neutral, and dried at 105°C for 4 hours. The dried material is then fully ground to obtain high-performance activated carbon, which can be used as a supercapacitor electrode material.

[0101] Comparative Example 2 :This comparative example provides a nitrogen in-situ doped super capacitor electrode material and a preparation method thereof, comprising the following steps:

[0102] (1) Using cotton as a carbon source material, 5 g of dried cotton and 2 g of Enteromorpha biomass were mixed;

[0103] (2) placing the mixed raw materials in a tubular furnace and pyrolyzing and carbonizing them at 550° C. for 1.5 h under a nitrogen atmosphere; the carbonized carbon material collected was about 30% of the raw materials, i.e., 2.4 g;

[0104] (3) 2 g of the carbonized carbon material was ground and mixed with 6 g of potassium hydroxide activator (mass ratio of 1:3) to prepare a 100 mL solution, which was then fully stirred;

[0105] (4) The impregnated material was filtered, dried at 105°C for 1 h, and placed in a tube furnace for activation at 750°C for 1.5 h under a nitrogen atmosphere;

[0106] (5) The activated material is neutralized with hydrochloric acid, washed with deionized water until neutral, and dried at 105°C for 4 hours. The dried material is then fully ground to obtain high-performance activated carbon, which can be used as a supercapacitor electrode material.

[0107] Comparative Example 3 :This comparative example provides a nitrogen in-situ doped supercapacitor electrode material and a preparation method thereof, comprising the following steps:

[0108] (1) Using coal liquefaction residue as a carbon source material, 5 g of dried coal liquefaction residue raw material and 2 g of Enteromorpha biomass were mixed;

[0109] (2) placing the mixed raw materials in a tubular furnace and pyrolyzing and carbonizing them at 550° C. for 1.5 h under a nitrogen atmosphere; the carbonized carbon material collected was about 30% of the raw materials, i.e., 2.1 g;

[0110] (3) 2 g of the carbonized carbon material was ground and mixed with 6 g of potassium hydroxide activator (mass ratio of 1:3) to prepare a 100 mL solution, which was then fully stirred;

[0111] (4) The impregnated material was filtered, dried at 105°C for 1 h, and placed in a tube furnace for activation at 650°C for 1.5 h under a nitrogen atmosphere;

[0112] (5) The activated material is neutralized with hydrochloric acid, washed with deionized water until neutral, and dried at 105°C for 4 hours. The dried material is then fully ground to obtain high-performance activated carbon, which can be used as a supercapacitor electrode material.

[0113] Comparative Example 4 :This comparative example provides a nitrogen in-situ doped super capacitor electrode material and a preparation method thereof, comprising the following steps:

[0114] (1) First, the coal liquefaction residue was carbonized in a tube furnace at 500° C. for 1 h, and then 5 g of the carbonized coal liquefaction residue and 2 g of Enteromorpha biomass were mixed;

[0115] (2) placing the mixed raw material obtained in step (1) in a tubular furnace and pyrolyzing and carbonizing at 550° C. for 1.5 h under a nitrogen atmosphere; collecting carbonized carbon material of about 30% of the raw material, i.e., 2.4 g;

[0116] (3) 2 g of the carbonized carbon material was ground and mixed with 6 g of potassium hydroxide activator (mass ratio of 1:3) to prepare a 100 mL solution, which was then fully stirred;

[0117] (4) The impregnated material was filtered, dried at 105°C for 1 h, and placed in a tube furnace for activation at 750°C for 1.5 h under a nitrogen atmosphere;

[0118] (5) The activated material is neutralized with hydrochloric acid, washed with deionized water until neutral, and dried at 105°C for 4 hours. The dried material is then fully ground to obtain high-performance activated carbon, which can be used as a supercapacitor electrode material.

[0119] Comparative Example 5 :This comparative example provides a supercapacitor electrode material and a preparation method thereof, comprising the following steps:

[0120] (1) First, the coal liquefaction residue was carbonized in a tube furnace at 500°C for 1 h, and then carbon fibers were prepared. Then, 5 g of carbon fibers and 2 g of Enteromorpha biomass were mixed;

[0121] (2) placing the mixed raw material obtained in step (1) in a tubular furnace and pyrolyzing and carbonizing at 550° C. for 1.5 h under a nitrogen atmosphere; collecting carbonized carbon material of about 30% of the raw material, i.e., 2.4 g;

[0122] (3) 2 g of the carbonized carbon material was ground and mixed with 6 g of potassium hydroxide activator (mass ratio of 1:3) to prepare a 100 mL solution, which was then fully stirred;

[0123] (4) The impregnated material was filtered, dried at 105°C for 1 h, and placed in a tube furnace for activation at 750°C for 1.5 h under a nitrogen atmosphere;

[0124] (5) The activated material is neutralized with hydrochloric acid, washed with deionized water until neutral, and dried at 105°C for 4 hours. The dried material is then fully ground to obtain high-performance activated carbon, which can be used as a supercapacitor electrode material.

[0125] Comparative Example 6 :This comparative example provides a supercapacitor electrode material and a preparation method thereof, comprising the following steps:

[0126] (1) First, the cotton was carbonized in a tube furnace at 500 °C for 1 h, and then 5 g of the carbonized cotton was mixed with 2 g of Enteromorpha biomass;

[0127] (2) placing the mixed raw material obtained in step (1) in a tubular furnace and pyrolyzing and carbonizing at 550° C. for 1.5 h under a nitrogen atmosphere; collecting carbonized carbon material of about 30% of the raw material, i.e., 2.4 g;

[0128] (3) 2 g of the carbonized carbon material was ground and mixed with 6 g of potassium hydroxide activator (mass ratio of 1:3) to prepare a 100 mL solution, which was then fully stirred;

[0129] (4) The impregnated material was filtered, dried at 105°C for 1 h, and placed in a tube furnace for activation at 750°C for 1.5 h under a nitrogen atmosphere;

[0130] (5) The activated material is neutralized with hydrochloric acid, washed with deionized water until neutral, and dried at 105°C for 4 hours. The dried material is then fully ground to obtain high-performance activated carbon, which can be used as a supercapacitor electrode material.

[0131] Comparative Example 7 :This comparative example provides a supercapacitor electrode material and a preparation method thereof, comprising the following steps:

[0132] (1) First, cotton was carbonized in a tube furnace at 800 °C for 1 h, and then carbon fibers were prepared. Then, 5 g of carbon fibers and 2 g of Enteromorpha biomass were mixed;

[0133] (2) placing the mixed raw material obtained in step (1) in a tubular furnace and pyrolyzing and carbonizing at 550° C. for 1.5 h under a nitrogen atmosphere; collecting carbonized carbon material of about 30% of the raw material, i.e., 2.4 g;

[0134] (3) 2 g of the carbonized carbon material was ground and mixed with 6 g of potassium hydroxide activator (mass ratio of 1:3) to prepare a 100 mL solution, which was then fully stirred;

[0135] (4) The impregnated material was filtered, dried at 105°C for 1 h, and placed in a tube furnace for activation at 750°C for 1.5 h under a nitrogen atmosphere;

[0136] (5) The activated material is neutralized with hydrochloric acid, washed with deionized water until neutral, and dried at 105°C for 4 hours. The dried material is then fully ground to obtain high-performance activated carbon, which can be used as a supercapacitor electrode material.

[0137] Comparative Example 8 :This comparative example provides an activated carbon electrode material and a preparation method

[0138] (1) Coal liquefaction residue was used as the carbon source material. 5 g of dried coal liquefaction residue raw material was placed in a tubular furnace and pyrolyzed and carbonized at 550° C. for 1.5 h in a nitrogen atmosphere. The carbonized carbon material collected was about 40% of the raw material, i.e. 2 g.

[0139] (3) Grind 2 g of the carbonized carbon material and mix with 6 g of potassium hydroxide activator to make a 100 mL solution, and then stir thoroughly;

[0140] (4) The impregnated material was filtered, dried at 105°C for 1 h, and placed in a tube furnace for activation at 750°C for 1.5 h under a nitrogen atmosphere;

[0141] (5) The activated material is neutralized with hydrochloric acid, washed with deionized water until neutral, and dried at 105° C. for 4 h. The dried material is then fully ground to obtain an activated carbon material.

[0142] Comparative Example 9: This comparative example provides a Enteromorpha-based carbon electrode material and a preparation method

[0143] Get Enteromorpha from seawater, wash with distilled water and dry. Take 5g of dried Enteromorpha and mix it with 3M KOH solution, soak for 24h, and then dry to obtain Enteromorpha-KOH precursor complex, and control the mass ratio of Enteromorpha to KOH to be 1:3. After gradually heating to 800℃ in a nitrogen atmosphere for carbonization activation for 2h, a carbonized sample is obtained. The obtained product is washed 3 times with 2M hydrochloric acid to neutralize excess NaOH and remove impurities, thereby removing impurities, and then washed with deionized water and filtered, and then the sample is placed in a 60℃ vacuum drying oven and dried for more than 8h to obtain Enteromorpha-based carbon electrode material.

[0144] Test Example 1:

[0145] In this test example, a three-electrode system was assembled with the supercapacitor electrode materials prepared in Examples 1 to 2 and Comparative Examples 1 to 9, and the relevant electrical properties of the obtained materials were tested.

[0146] Take the capacitor electrode materials prepared in Examples 1 to 2 and Comparative Examples 1 to 9, mix them with conductive graphite and binder polytetrafluoroethylene in a mass ratio of 8:1:1, add an appropriate amount of organic solvent (ethanol), grind them into a uniform slurry in an agate mortar, apply them on the foam nickel current collector, and then place them in a 60°C blast drying oven for 12 hours. After drying, press them to 5 to 20 MPa with a tablet press to make a working electrode, with a metal platinum sheet electrode as the counter electrode, a 5Hg / HgO electrode as the reference electrode, and a 6M KOH solution as the electrolyte solution. The assembled three-electrode systems were tested for electrochemical performance on the LAND battery test system.

[0147] like Figure 5 As shown in the figure, the CV curve tested under multiple voltages can reflect the electrochemical reactions of the electrode at different potentials. By changing the voltage and performing multiple measurements, the redox reactions occurring in different potential intervals can be observed, thereby gaining a more comprehensive understanding of the electrochemical properties of the electrode. It can be seen that the curve is an obvious carbon material curve, and the position, shape, and symmetry of the oxidation peak and reduction peak show that the electrode reaction is reversible.

[0148] like Figure 6 As shown, the supercapacitor electrode material obtained in Example 1 is 1Ag -1 At a current density of 200 F g -1 .

[0149] like Figure 7 As shown, the supercapacitor electrode material obtained in Example 1 is 5Ag -1 Under the current density, after 5000 cycles of charge and discharge, its capacitance retention rate can reach 95.6%, which has good cycle characteristics and good stability.

[0150] The specific test results are shown in Table 2:

[0151] Table 2

[0152]

[0153]

[0154] From the data in Table 2, it can be seen from Examples 1 to 2 that although both are doped with nitrogen-containing Enteromorpha, the blending ratio of nitrogen-containing Enteromorpha in Example 1 is better, the material has rich specific surface area, and has a larger specific capacitance;

[0155] Compared with Example 1, a large amount of Enteromorpha was added in Comparative Example 1, but the excessive Enteromorpha would reduce the carbonization effect of the material, resulting in a decrease in the electrochemical performance of the final carbon electrode material, especially a serious decrease in the capacitance retention rate to 80.4%;

[0156] Compared with Example 1, Comparative Example 2 uses cotton and Enteromorpha as carbon sources. Since the carbon content in cotton biomass is far less than the liquefied residue added in Example 1, the carbon structure during the carbonization process is affected and the electrochemical performance is reduced.

[0157] Compared with Example 1, the activation temperature in Comparative Example 3 is lower, the activation of the raw material is insufficient, the specific surface area is reduced, and the electrochemical performance of the material is reduced;

[0158] Compared with Example 1, in Comparative Example 4, the coal liquefaction residue is first carbonized and then the Enteromorpha biomass is added. Nitrogen mainly acts as a blending agent and is difficult to embed into the carbon skeleton, which cannot enhance the electronic transmission of the material. Therefore, its electrochemical performance is significantly reduced.

[0159] Compared with Example 1, in Comparative Example 5, the carbonized coal liquefaction residue is made into carbon fibers and then mixed with Enteromorpha biomass. In this process, Enteromorpha biomass is also mixed with carbon fibers, and nitrogen atoms are not effectively embedded in the carbon skeleton, which affects its electrochemical performance.

[0160] Compared with Example 1, in Comparative Example 6, carbonized cotton is made into carbon fibers and then mixed with Enteromorpha biomass. This process is also a blending process, and the nitrogen atoms cannot be effectively embedded in the carbon skeleton, which affects its electrochemical performance.

[0161] Compared with Example 1, in Comparative Example 7, cotton is first carbonized at 800°C to make carbon fibers and then mixed with Enteromorpha biomass. On the one hand, this process is only a blending process. On the other hand, the carbonization temperature is too high, which will reduce its specific surface area in the later activation process, thereby reducing its electrochemical performance.

[0162] Compared with Example 1, in Comparative Example 8, only the liquefied residue is carbon material, and its electrochemical performance is poor. In Example 1 of the present invention, nitrogen-containing Enteromorpha is doped, and its specific surface area is larger, the mesopores are richer, the equivalent resistance is lower, and the electrochemical performance is poor. -1 The specific capacitance (F / g) is larger and the capacitance is maintained for many cycles;

[0163] Specific as Figure 7 and Figure 8 As shown in the BET diagram, the specific surface area of ​​the activated carbon electrode material prepared in Comparative Example 8 is 1227.3 m 2 / g, and the pore size distribution is mostly less than 2nm, mainly micropores, which is a typical feature of double-layer capacitor charging and discharging.

[0164] Compared with Example 1, in Example 9, only Enteromorpha is used as the carbon material, and its specific surface area is insufficient and the electrochemical performance is poor, which indicates that the nitrogen atoms in Enteromorpha can play a synergistic effect on the carbon structure of the liquefied residue.

[0165] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nitrogen in-situ doped supercapacitor electrode material, characterized in that: Specifically, coal liquefaction residue is used as the main carbon source material, and Enteromorpha is used as the nitrogen source and secondary carbon source material. The coal liquefaction residue and Enteromorpha are mixed, and then carbonization, impregnation, activation and neutral washing processes are carried out in sequence to obtain nitrogen in-situ doped supercapacitor electrode materials.

2. The preparation method according to claim 1, characterized in that The coal liquefaction residue is a tetrahydrofuran insoluble substance produced during the coal liquefaction process, and has a carbon content of 80% to 90%; the enteromorpha has a carbon content of 25% to 30% and a nitrogen content of about 3% to 4%; Preferably, the mass ratio of the coal liquefaction residue to Enteromorpha is 1:0.2-0.

5.

3. The preparation method according to claim 1, characterized in that: The specific operation is to mix the coal liquefaction residue which is dried at 90-120°C for 1-2 hours and then crushed through a 50-mesh sieve with the enteromorpha which is vacuum dried at 95-125°C for 2-5 hours and then ground through a 100-mesh sieve. Preferably, the carbonization and activation are performed under an inert atmosphere, and more preferably, the inert atmosphere is nitrogen.

4. The preparation method according to claim 1, characterized in that: The carbonization temperature is 400-600° C. and the time is 1-2 hours.

5. The preparation method according to claim 1, characterized in that: The impregnation is to grind the carbonized material, add an activator to form a solution and stir; preferably, the activator is selected from one or more of KOH, NaOH, ZnCl2 and K2CO3; further preferably, the activator is KOH; Preferably, the mass ratio of the activator to the carbonized material is 2:1 to 4:

1.

6. The preparation method according to claim 1, characterized in that: The activation temperature is 700-900° C. and the activation time is 1-1.5 hours. Preferably, the solvent used in the acidification process is selected from one or more of hydrochloric acid and nitric acid; further preferably, the solvent is hydrochloric acid; Preferably, the neutralization washing process specifically comprises acidifying and neutralizing the activated material, washing it with deionized water until it is neutral, and then drying it at 95 to 120° C. for 2 to 4 hours and then fully grinding it to obtain a nitrogen in-situ doped supercapacitor electrode material.

7. A nitrogen in-situ doped supercapacitor electrode material, characterized in that: The supercapacitor electrode material is prepared by the method for preparing the supercapacitor electrode material according to any one of claims 1 to 6.

8. A battery negative electrode, characterized in that: A supercapacitor electrode material doped in situ with nitrogen prepared by the preparation method according to any one of claims 1 to 6 as an active material; Preferably, the battery negative electrode further comprises a conductive material, a binder and an organic solvent; Wherein, the conductive material is selected from one or more of acetylene, acetylene black, and conductive graphite, and is more preferably conductive graphite; The binder is one or more of polytetrafluoroethylene and polyvinylidene fluoride, and polytetrafluoroethylene is more preferred; The organic solvent is selected from one or more of ethanol, 1-methyl-2-pyrrolidone, and N-methylpyrrolidone, and is more preferably ethanol. Preferably, the mass ratio of the active substance, the conductive material and the binder is 7:1:1 to 9:1:1; further preferably, the mass ratio of the active substance, the conductive material and the binder is 8:1:

1.

9. A supercapacitor, characterized in that: A battery negative electrode comprising the battery negative electrode of claim 8; Preferably, the supercapacitor further comprises a positive electrode, a separator, and an electrolyte; Further preferably, the electrolyte is a 6M KOH solution.

10. Use of the nitrogen in-situ doped supercapacitor electrode material according to claim 7 in capacitor energy storage devices and electrode materials.

Citation Information

Cited By

  • Sulfur-doped coal-based porous carbon supercapacitor electrode material and preparation method thereof

    CN120977780A